Malnutrition in Children at General Tinio, Nueva Ecija and the Assimilation of Interventions to Prevent the Condition - Reguyal, June Christian G.; Gamiao, Kristhine Abegail M. (Proceedings Series on Health & Medical Sciences, 2025)
Undernutrition is a complex issue that affects various aspects of life. Malnutrition increases the risk of various diseases and infections. Undernutrition can also lead to chronic health conditions such as obesity and diabetes. The study aims to determine the malnutrition among children below five years old at General Tinio, Nueva Ecija. The study analyzed a population of 3,693 children aged 0–5 years old from General Tinio, Nueva Ecija, based on data from the 2022 Nutrition Survey conducted by the Municipal Health Office. Using a total population sampling technique, the entire dataset was included to ensure comprehensive representation. Nutritional assessments were conducted following the World Health Organization (WHO) Classification of Nutritional Status of Infants and Children, with variables such as weight-for-age, height-for-age, and BMI-for- age analyzed against WHO standards. Data analysis employed descriptive statistics to determine the prevalence and severity of malnutrition (stunting, wasting, underweight, overweight, and obesity). Results were categorized, presented in tables, and compared across genders to identify disparities, with trends and risk factors interpreted in line with global and local benchmarks. Results: The overall prevalence of overweight is 6.04%, and the prevalence of obesity is 6.15%. Overall, undernutrition specifically overweight and obesity is also a concern for children aged 0-5 years old with a significant proportion of children in the overweight and obese categories. The global prevalence of obesity in children and adolescents aged 5-19 years has increased from 0.7% to 5.6% for girls and from 0.9% to 7.8% for boys from 1975 to 2016. In the United States, 1 in 5 children and adolescents are affected by childhood obesity. The American Academy of Pediatrics has issued its first comprehensive guideline on evaluating and treating children and adolescents with obesity, which reflects growing concerns about health later in life. The guideline recommends that pediatricians try to see children with obesity and provide comprehensive programs to help them manage their weight. Childhood obesity is a complex issue that can be caused by many factors, including behavior, genetics, and societal and community factors such as access to healthy food and beverages.